2013
DOI: 10.1016/j.jenvman.2013.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Economic implications of reducing carbon emissions from energy use and industrial processes in Brazil

Abstract: This study assesses the economy-wide impacts of cutting CO2 emissions on the Brazilian economy. It finds that in 2040, the business-as-usual CO2 emissions from energy use and industrial processes would be almost three times as high as those in 2010 and would account for more than half of total national CO2 emissions. The current policy aims to reduce deforestation by 70 percent by 2017 and lower emissions intensity of the overall economy by 36-39 percent by 2020. If the policy were implemented as planned and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…However, currently, in the face of international pressure to curb carbon releases as well as the tight domestic fossil-energy supply [16], relative indicators are usually applied for measuring carbon reduction target in order to avoid the possible negative impacts on local economic development [17]. For example, a case study for Brazil shows that the business-as-usual CO 2 emissions in 2040 from energy use and industrial processes would be almost three times as high as those in 2010, while the current policy aims to lower emissions intensity of the overall economy by 36-39 percent by 2020 [18]. Another analysis on carbon reduction in China indicates that the region with a lower reduction benchmark and higher decoupling elasticity value has more difficulty in achieving the emission reduction targets without powerful relevant policy [19], and a provincial level case study illustrates that with the rapid economic development, CO 2 emission in Jiangsu province rose from 1, 88 × 10 8 t in 1995 to 5, 20 × 10 4 t in 2009, with an average annual growth rate of 7.54% [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, currently, in the face of international pressure to curb carbon releases as well as the tight domestic fossil-energy supply [16], relative indicators are usually applied for measuring carbon reduction target in order to avoid the possible negative impacts on local economic development [17]. For example, a case study for Brazil shows that the business-as-usual CO 2 emissions in 2040 from energy use and industrial processes would be almost three times as high as those in 2010, while the current policy aims to lower emissions intensity of the overall economy by 36-39 percent by 2020 [18]. Another analysis on carbon reduction in China indicates that the region with a lower reduction benchmark and higher decoupling elasticity value has more difficulty in achieving the emission reduction targets without powerful relevant policy [19], and a provincial level case study illustrates that with the rapid economic development, CO 2 emission in Jiangsu province rose from 1, 88 × 10 8 t in 1995 to 5, 20 × 10 4 t in 2009, with an average annual growth rate of 7.54% [20].…”
Section: Introductionmentioning
confidence: 99%
“…With this understanding, the definition of green industry includes various activities from product design, material use, energy source use, machine selection, process design (location, layout, work system design), production processes, product handling (main, side, waste), to the distribution or product logistics. Chen (2013) showed that environmental knowledge is a series of ecological knowledge that individuals have about the environment. Knowledge about the environment can affect consumer attitudes.…”
Section: Literature Review the Influence Of Knowledge On The Application Of Green Manufacturing Iggy Adbaidainymentioning
confidence: 99%
“…Researchers and academics offer different perspectives on which instrument is better. For instance, some argue that a carbon tax is a more efficient method than an ETS, by stating that such a policy can act directly on issues related to equity and distribution, through different forms of recycling revenues [27][28][29][30][31][32]. In addition, the tax value is known by all economic agents and it does not change frequently as in the ETS, offering more security and stability [33][34][35][36].…”
Section: Defining and Designing Carbon Pricing Instrumentsmentioning
confidence: 99%